O contexto socioambiental Amazônico e o ensino de Ecologia no olhar de professores de Biologia - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The Amazon region is world-renowned for its exuberance, or for the environmental services offered to Brazil and the world. At the same time that it has a wealth of natural resources, the Amazon presents socio-environmental problems. The study of ecology can provide the student with a better understanding of the functioning of the ecosystem and of the changes associated with the region and also enables reflection on the imbalances that have occurred in the Amazon. This work had the objective of analyzing the difficulties and didactic-pedagogical possibilities of Biology teachers regarding the teaching of ecology with a focus on the Amazonian socio-environmental context. This study is based on a qualitative research perspective. We used as data collection instrument questionnaires and semi-structured projected audio-video interviews. To analyze the data, the content analysis method was used. For the organization of the results, three units of analysis were chosen, the first one being named: "The teaching of Amazon ecology in the Amazon" with the categories: natural / conceptual ecology, conservation ecology, human/social/political ecology). The second unit of analysis is titled Difficulties/non-ecology teaching of the Amazon, with the categories: initial formation, didactic-pedagogic, demotivation. Finally, the third unit of analysis: field lessons in science, with some reports of support to the classes of activities, by some teachers and, because they are part of teaching, have often returned only to the specific biological original. Subjects of a natural vision of the environment are discussed, since teachers, when taking their students to a field class, aim at the editing and appreciation of nature. The results show that a natural and conceptual approach to ecology is predominant in their discourses. Other ideologies of the other ethnologies were those on which the human, social and cultural element were most prominent. The socio-environmental problems are implemented when there is a national repercussion or when the community is affected by a socio-environmental problem. The difficulties of training and not studying textbooks about the region are not curricular and didactic, and culminate in the teacher's demotivation.
Keywords: Ecologia; Temas socioambientais; Formação de professores; CIÊNCIAS EXATAS E DA TERRA